Improving rice yield and water productivity in dry climatic zones of West Africa: Season-specific strategies - Johnson, J.M.; Becker, M.; Dossou-Yovo, Elliott Ronald; Saito, Kazuki (Elsevier, 2024)
Context: Irrigated lowland systems contribute most to rice production in sub-Saharan Africa and play a critical role in meeting the increasing rice demand. However, in dry areas of West Africa, negative effects associated with climate change and widespread water scarcity hamper efforts to increase the productivity of irrigated rice. Quantifying rice yields and water productivity and identifying the drivers for the prevailing variability can aid in the targeting and dissemination of appropriate soil, water, and crop management practices. Objective: The main objectives of this research were: (i) to quantify the rice yield gap in representative irrigated systems in dry areas of West Africa, both in wet and dry seasons, and identify factors that can contribute to narrowing the gap, and (ii) to assess the trade-offs or synergies between productivity and resource (water and fertiliser) use efficiency. Methods: We monitored 203 and 192 smallholder farmers’ fields in the wet and dry seasons, respectively, in four contrasting irrigation schemes in Burkina Faso from 2018 to 2020 and assessed key performance indicators (grain yield, water productivity, and nutrient use efficiency). We calculated rice yield gaps (difference between exploitable and actual farmer yields) and identified the drivers of variability of yield and water productivity using machine learning and Shapley Additive exPlanations (SHAP) feature importance. Results: Indicators of productivity and sustainability differed between irrigation schemes and seasons. Rice yield was higher in wet (5.3 Mg ha− 1 ) than in dry seasons (3.7 Mg ha− 1 ), while the variability was higher in the dry (CV = 46%) than in the wet seasons (CV = 29%). Also, the yield gap was slightly higher in the dry (36%) than in the wet seasons (31%). While differences in the number of seedlings per hill and the source of seeds were the key drivers of yield variability in wet-season rice, the split of N fertilizer applications, bird control, and the soil dryness index were the most important in dry-season rice. Furthermore, within seasons, high-yielding fields had higher water productivity, and N, P, and K use efficiencies. Conclusion: These findings suggest that rice yields can be increased without trade-offs with water productivity and nutrient use efficiencies. Significance: This is the first study highlighting the season-specificity of determinants of variability of yield and water productivity in irrigated rice in West Africa. Improved water and fertilizer management can contribute to achieving the dual goal of narrowing the yield gap and improving water productivity, while increasing nutrient use efficiency, particularly in the dry season.